1990
DOI: 10.1128/aem.56.11.3473-3477.1990
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Chloroperoxidase on Aminopropyl-Glass

Abstract: Chloroperoxidase (CPO) purified from Caldariomyces fumago CMI 89362 was covalently bound to aminopropyl-glass by using a modification of an established method. Acid-washed glass was derivatized by using aminopropyltriethoxysilane, and the enzyme was ionically bound at low ionic strength. Further treatment with glutaraldehyde covalently linked the enzyme to the glass beads in an active form. No elution of bound activity from glass beads could be detected with a variety of washings. The loading of enzyme protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 26 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…48,55 Reaction engineering Immobilization Immobilization of peroxygenases has been evaluated manifold to increase their stability. For example covalent immobilization of CfuCPO to glass, 64 hydrophilic polymers, 65 mesoporous silica, 66,67 ferromagnetic magnetic beads, 68 chitosan membranes, 69,70 on agarose gels, 71 as cross-linked enzyme aggregates, 72,73 or encapsulation in PEG-doped silica matrices, 74 have been evaluated. Even though in most of…”
Section: Protein Engineeringmentioning
confidence: 99%
“…48,55 Reaction engineering Immobilization Immobilization of peroxygenases has been evaluated manifold to increase their stability. For example covalent immobilization of CfuCPO to glass, 64 hydrophilic polymers, 65 mesoporous silica, 66,67 ferromagnetic magnetic beads, 68 chitosan membranes, 69,70 on agarose gels, 71 as cross-linked enzyme aggregates, 72,73 or encapsulation in PEG-doped silica matrices, 74 have been evaluated. Even though in most of…”
Section: Protein Engineeringmentioning
confidence: 99%
“… Enzyme Carrier (Interaction) Immobilisation yield Recovered activity Reaction catalysed Remarks Ref. Carrier-bound approaches Cfu CPO Aminopropyl glass (covalent) 91% TMPD oxidation Improved storage stability ( Kadima and Pickard, 1990 ) Cfu CPO Methacrylate polymer (covalent) n.d. 83% Monochloro-dimedon chlorination Storage and thermal stability increased ( Bayramoglu et al, 2011 ) Cfu CPO Mesoporous silica (covalent) 11% n.d. Azo dye oxidation Increased temperature stability and k cat / K M ( Guerrero et al, 2012 ) Cfu CPO Mesoporous silica (adsorptive) 80% n.d. Styrene oxidation Increased stability against temperature and acetonitrile ( Águila et al, 2011 ) Cfu CPO Magnetic beads (covalent) n.d. 58% Monochloro-dimedon chlorination Improved thermal and storage stability ( Bayramoğlu et al, 2008 ) Cfu CPO Chitosan (covalent) n.d. n.d. Monochloro-dimedon chlorination Improved thermal and oxidative stability ( Zhang et al, 2009 ) Cfu CPO Agarose (adsorptive) 75% 50% Monochloro-dimedon chlorination Increased stability against tert -butyl hydroperoxide ( Pešić et al, 2012 ) Cfu CPO Agarose (covalent) …”
Section: Reaction and Medium Engineering Approachesmentioning
confidence: 99%
“…An example of tailoring the surface of MPS was observed with the immobilisation of catalytically active and stable chloroperoxidase. Previous work 38 had shown that CPO could be adsorbed in a catalytically active manner on amino-propyl modified glass beads. A series of amino modified periodic mesoporous silicates was prepared by varying the composition ratio of the silica precursors 39 (tetraethoxysilane and bis- [3-(trimethoxysilyl)propyl]amine) used.…”
Section: Immobilisation Of Enzymes By Adsorptionmentioning
confidence: 99%